Resurrecting Janus in the twentieth century history of medicine and science - Haalboom, Floor (Studium, 2019)
This article analyses the history of the journal Janus (1896-1989), the meaning of the Janus metaphor, and the reception of the journal in the fields of history of medicine and science. It makes three general arguments. First, Janus was a much more important publication in the history of medicine than acknowledged in the field. Second, at the time of the journal’s founding, the Janus head metaphor had broader significance in debates on how the natural sciences and the humanities should relate to one another, and on what medical history ideally looked like. Third, the very different reception of Janus in the history of science and the history of medicine is proof of the traditionally strong, but artificial boundary between those fields.